English for specific purposes = Tiếng Anh chuyên ngành - Nguyễn Thị Hồng Anh (Trường Đại học Thuỷ Lợi, 2020)
Unit 1: what is engineering; Unit 2: Civil engineering; Unit 3: Water; Unit 4: Building material ; Unit 5: Environmental engineering;Unit 6: Maths and measurement; Unit 7: Safety Equipment; Unit 8: Power tools; Unit 9: Site layout; Unit 10: Scientific method